ISLAMIC STUDY: CULTURAL ASPECTS (HISTORIC MOSQUES) - Satria Effendi; Mahmid Arifi (Universitas Muhammadiyah Surakarta, 2023)
Mosques have an important history in Islam and are also one of the most important aspects in the spread of Islam. The mosque is also a place of worship for Muslims, besides that the mosque is also a center for Muslim activities, such as ta'lim activities for the surrounding community, educational activities, deliberations on Islamic religious activities and so on. The role and function of the mosque also experienced extraordinary development. Mosques not only serve as the main support for ritual worship activities that function to improve mental and spiritual health, but have also been used for various other social activities. The role and function of the mosque also experienced extraordinary development. Mosques not only serve as the main support for ritual worship activities that function to improve mental and spiritual health, but have also been used for various other social activities. Likewise, the architectural design of the mosque, its name, program, management, characteristics of the congregation and others have also experienced remarkable improvements.